2021
DOI: 10.21014/acta_imeko.v10i4.1144
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy grid mapping for rover navigation based on semantic segmentation

Abstract: Obstacle mapping is a fundamental building block of the autonomous navigation pipeline of many robotic platforms such as planetary rovers. Nowadays, occupancy grid mapping is a widely used tool for obstacle perception. It foreseen the representation of the environment in evenly spaced cells, whose posterior probability of being occupied is updated based on range sensors measurement. In more classic approaches, the cells are updated to occupied at the point where the ray emitted by the range sensor encounters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The results showed that the model presented good results in the detection of t-shirts with an average precision of 95 %. Furthermore, several studies [34]- [37] presented methods to segment objects using CNNs which have similarities to the implementation used and modelized for the garment segmentation and classification. Table 2 summarizes the main results of the segmentation and classification methods analysed.…”
Section: Solution Descriptionmentioning
confidence: 99%
“…The results showed that the model presented good results in the detection of t-shirts with an average precision of 95 %. Furthermore, several studies [34]- [37] presented methods to segment objects using CNNs which have similarities to the implementation used and modelized for the garment segmentation and classification. Table 2 summarizes the main results of the segmentation and classification methods analysed.…”
Section: Solution Descriptionmentioning
confidence: 99%
“…In [37], a terrain segmentation model is proposed using PSPNet [38], trained by real rover-based images from Mars and artificial images generated by the Unity3D software, aiming to automate a path planning algorithm on the Martian surface. In [39], authors propose a methodology for path rerouting using imagery data, depth maps and a CNN-based neural network trained with Katwijk beach planetery rover dataset, in order to detect and avoid obstacles such as rocks and boulders.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial use of terrain classification in planetary environments is the path planning optimization [36]. In [37], a deep learning model for terrain segmentation is proposed using PSPNet [38] model, trained by real rover-based images from Mars and artificial images generated by the Unity3D software, aiming to automate a path planning algorithm on the Martian surface while in [39], authors propose a methodology for path rerouting using imagery data, depth maps and a CNN-based neural network trained with Katwijk beach planetery rover dataset, aiming to detect and avoid obstacles such as rocks and boulders.…”
Section: Introductionmentioning
confidence: 99%